Adopting Servitization: A review of the impact and challenges in the Manufacturing firms - GONZALEZ HERNANDEZ, ANTONIO (2016)
The purpose of the research reported in this paper has been to gain through a review on the existing literature a deeper understanding of the impact in a manufacturing firm when is adopted a Servitization strategy and to summarize the key challenges that a typical manufacturer experiences when is followed such business model.